DAMPAK CELEBRITY ENDORSER TERHADAP MINAT BELI PRODUK CAFFINO MELALUI EKUITAS MEREK SEBAGAI VARIABEL INTERVENING - Nurdiana Haddad Assalam; Aryo Wibisono (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2020)
Nowadays, coffee has become part of the lifestyle of all groups, both young people and adults, with it making companies happy to win the right market strategy to win the market. As is done by PT Sumber Kopi Prima which promotes its product in the form of Caffino by using the celebrity endorser strategy. The purpose of this study is to determine the impact of celebrity endorsers on buying interest in Caffino products through brand equity as an intervening variable. The method used was purposive sampling. And the results of this study are celebrity endorser has no impact on purchase intention, and brand equity has an impact on purchase intention, while the indirect effect of celebrity endorser on purchase intention through brand equity has a positive and significant effect.